Extracts from Cordyceps cicadae and Hericium erinaceus promote the neurite outgrowth of retinal ganglion cells - Fang-Yi Chen; Chin-Chu Chen; Chuan-Chin Chiao (PLoS ONE, 2026)
The regenerative capacity of mammalian RGC neurites after damage, such as glaucoma, is limited. Numerous studies have utilized herbal extracts to promote neural regeneration and exert neuroprotective effects in the hope of mitigating glaucoma. In the present study, we investigated the effect of extracts from the cicada fungus ( Cordyceps cicadae ) and the Lion’s mane mushroom ( Hericium erinaceus ) on neurite outgrowth of retinal explants and isolated RGCs. We also examined whether these extracts affect the number of apoptotic cells and neurite outgrowth activity of RGCs. The results showed that an aqueous extract of Cordyceps cicadae , an ethanol extract of Hericium erinaceus , and the purified compound Erinacine Sare able to promote neurite outgrowth in retinal explants. Given its role as a key bioactive compound, Erinacine S was further investigated on isolated RGCs, where it also significantly enhanced neurite outgrowth, demonstrating a direct effect on RGC regeneration. In addition, these extracts have no significant drawbacks in terms of cell apoptosis and RGC neurite outgrowth activity at specific concentrations. The present study thus demonstrates that while excessively high concentrations of these extracts may inhibit neurite growth, at moderate concentrations some extracts from Cordyceps cicadae and Hericium erinaceus have the potential of promoting neurite regeneration in the mammalian retina. Further research targeting the molecular mechanisms behind these effects may shed light on their potential application as a medicine or nutraceutical for facilitating neural regeneration.